2020
DOI: 10.1155/2020/6126210
|View full text |Cite
|
Sign up to set email alerts
|

Testing Positive and Disclosing in Pregnancy: A Phenomenological Study of the Experiences of Adolescents and Young Women in Maseru, Lesotho

Abstract: The routine antenatal screening through the prevention of mother to child transmission of HIV (PMTCT) services results in pregnancy being often the point at which an HIV diagnosis is made. Disclosure to partners presents particular complexities during pregnancy. However, research on the pattern and experiences of disclosure in pregnancy is limited in Lesotho, despite the high prevalence of HIV among pregnant women. The aim of this study was to explore and describe the disclosure experiences of adolescent girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Existing studies have shown that early sexual debut is a significant risk factor for both unintended pregnancies and HIV infection due to various factors such as limited knowledge about safe sex practices, lack of access to contraceptives, and potential engagement in risky sexual behaviours [38,39]. This may also be linked to adolescent mothers learning of their HIV status for the first time when they confirm that they are pregnant [30,40]. This review also highlights that adolescent mothers are more likely to be involved in relationships where they have poor relationship power, gender inequitable norms, intimate partner violence, and little HIV preventive communication with higher-risk partners [43,44, 41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that early sexual debut is a significant risk factor for both unintended pregnancies and HIV infection due to various factors such as limited knowledge about safe sex practices, lack of access to contraceptives, and potential engagement in risky sexual behaviours [38,39]. This may also be linked to adolescent mothers learning of their HIV status for the first time when they confirm that they are pregnant [30,40]. This review also highlights that adolescent mothers are more likely to be involved in relationships where they have poor relationship power, gender inequitable norms, intimate partner violence, and little HIV preventive communication with higher-risk partners [43,44, 41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Early research found that pregnant women believed ANCs provided inadequate information about care, particularly HIV testing (Carlsson et al, 2021). Furthermore, some pregnant women perceived HIV testing in antenatal care as compulsory, indicating a lack of autonomy in decision-making (Madiba & Putsoane, 2020). Coercive HIV testing procedures can be a substantial obstacle to HIV testing during pregnancy (Razzaq et al, 2021), as they violate the concepts of autonomy and informed decision-making (Marchant et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…AOR from our analysis suggested that a considerable difference between women and men. HIV testing in antenatal care (Madiba & Putsoane, 2020). In Lesotho, women in the age range of 25-29 frequently experience childbirth (Ministry of Health & ICF International, 2016).…”
Section: ⅴ Discussionmentioning
confidence: 99%